Regional Integration through CPEC: Challenges and Opportunities - Aqeela Asif; Syed Qandil Abbas; Nasir Khan, (ASIAN Journal of International Peace & Security (AJIPS), 2022)
Regional connectivity is considered as an effective source of regional and international integration. The China-Pakistan Economic Corridor (CPEC) is going to be such an effective source to extensively attract regional and international attention. Pakistan has been confronting economic challenges ever since its independence and facing the issues of fragile economy which is one of the major causes of other socio-political issues as well. For instance, one of the key outcomes of poverty is the phenomena of terrorism and intolerance in the society. Therefore, China-Pakistan Economic Corridor (CPEC) will be an important step to change the destiny of developing countries like Pakistan and other states of the region in different sectors in general and in poverty elevation in particular. Now the question arises how CPEC is an effective attempt to address the issues of socio-economic development and how this project can play its role to provide foundation for regional and international integration? This study is based on liberalist perspective and focuses on diverse approaches, methods and plans related to economic development and will be a source of solid socio-economic growth of Pakistan.